Study of the leisure influence on attitude for leisure and mental health in a sample of portuguese seniors (Revista Lusófona de Educação, 2018)
Increased human longevity has been attributed to technological and medical advances, as well as improved hygiene and nutritional conditions, access to health care, changes in eating habits and cognitive development strategies (Osório, 2007). The present study examined the influence of leisure actions in the psychological well-being, leisure attitude and distress of seniors. The sample consisted of 403 participants (37,2% male; 62,8% female). Concerning the perception of health condition, 82,6% subjects were considered independent and 17,4% participants were considered dependent. The instruments used were the MHI (Ribeiro, 2001) and the LAS (Freire & Fonte, 2007). Main results exposed that participants in leisure activities presented high level of well-being and attitude for leisure (p